Friendship in doubt: Aleister Crowley, J.F.C. Fuller, Victor B. Neuburg, and British agnosticism - Kaczynski, Richard (Oxford studies in Western esotericism, 2024)
Rebelling against Victorian religious and social strictures, occultist Aleister Crowley, soldier J.F.C. Fuller, and poet Victor Neuburg were active contributors and participants in the British secularist movement at the dawn of the twentieth century. 'Friendship in Doubt' examines how the Agnostic movement inspired and introduced them to each other as foundational figures in the new religious movement of Thelema.